Biodegradable and injectable curcumin-loaded hydrogel for the prevention of postoperative intrauterine adhesion - Yang, Qingmei; Xu, Han; Chen, Yang; Jin, Xiaofen; Wu, Qing (Frontiers in Bioengineering and Biotechnology, 2025)
Intrauterine adhesions (IUAs) are essentially fibrosis of the endometrium within the uterine cavity. It is a common cause of infertility in women and seriously affects their physical and mental health. Current therapeutic strategies have failed to reach satisfactory outcomes. Injectable and self-healing uterine hydrogels with antifibrotic properties would be efficient in preventing IUA. In this work, we prepared curcumin-loaded carboxymethyl chitosan (CMC)–oxidized hyaluronic acid (OHA) intrauterine hydrogel (Cur@CMC-OHA hydrogel) with antifibrotic properties, and its injectable and self-healing properties could be adapted to the morphostructures of the uterine cavity. The hydrogels exhibited tissue adhesive power, which is ideal for stable uterine cavity retention and therapeutic outcomes. In vivo experiments showed that in situ injection of the Cur@CMC-OHA hydrogel into a mouse model of IUA reduced fibrotic tissues, prevented IUA, and improved the reproductive outcomes. It effectively downregulated fibrosis-associated transforming growth factor-β1 (TGF-β1) expression and reversed epithelial–mesenchymal transition (EMT), resulting in anti-fibrotic and fertility restoration. In conclusion, Cur@CMC-OHA hydrogel may be a promising alternative for clinical treatment of uterine adhesion.